ALTERNATIVE METHOD FOR DETERMINING METAL UPTAKE FROM WATER BY ESCHERICHIA COLI K12 CD3 - N. M. T. Jebril; A. K. Murad; R. A. Majeed; A. H. Al-Sabary; I. A. Abed; B. H. Hashim (مجلة الأنبار للعلوم الزراعية, 2025)
Bacteria are usually applied in biotechnology in areas such as element adsorptions due to extracellular/intracellular accumulation. Electron microscopes and spectrophotometry have shown proximate/accurate methods for observing and detecting these accumulated elements. In contrast, X-ray fluorescence (XRF) validates the examination of elements, and direct investigation for studying these collected elements. This research assessed the prospects for applying XRF in examining samples of bacterial-accumulated cadmium, Escherichia coli K12 Cd3, from artificial wastewater (AWW) by comparing the commonly used techniques of transmission electron microscopy (TEM-EDX) and inductively-coupled plasma mass spectrometry (ICP-MS). The results document a new means for using the XRF device in determining accurate quantities of cadmium accumulated in bacterial cells. By comparison, usual TEM-EDX analyzes show that the concentration was not qualitatively determined. At the same time, the ICP-M device was not as efficient in measuring cadmium concentrations. Finally, the findings show that an XRF device directly measures the element within bacterial cells with greater accuracy than those analyzed by TEM-EDX and ICP-MS devices. This demonstrates that XRF can be applied in various areas of biotechnology to investigate the absorption of accumulated elements and to explain the procedures underlying the biotechnology process